2010
DOI: 10.1186/1423-0127-17-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic copy number variants in sib pairs both affected with schizophrenia

Abstract: BackgroundSchizophrenia is a complex disorder with involvement of multiple genes.MethodsIn this study, genome-wide screening for DNA copy-number variations (CNVs) was conducted for ten pairs, a total of 20 cases, of affected siblings using oligonucleotide array-based CGH.ResultsWe found negative symptoms were significantly more severe (p < 0.05) in the subgroup that harbored more genetic imbalance (n ≧ 13, n = number of CNV-disrupted genes) as compared with the subgroup with fewer CNVs (n ≦ 6), indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Although STK11 deletions are present in Peutz-Jeghers syndrome, one case with an unusually large STK11 deletion has been described in which Peutz-Jeghers syndrome, mental retardation, and schizophrenia co-occurred (50). Similarly, a genome-wide screen in siblings co-affected by schizophrenia found reduced copy numbers of STK11 in 3 of 18 individuals, significantly more often than in control subjects (51). Of interest, STK11, also known as liver kinase B1, triggers phosphorylation of tau (52), and amyloid precursor protein overexpression promotes tau phosphorylation in an liver kinase B1-dependent manner (53).…”
Section: Genetics Of Psychosis In Alzheimer’s Diseasementioning
confidence: 96%
“…Although STK11 deletions are present in Peutz-Jeghers syndrome, one case with an unusually large STK11 deletion has been described in which Peutz-Jeghers syndrome, mental retardation, and schizophrenia co-occurred (50). Similarly, a genome-wide screen in siblings co-affected by schizophrenia found reduced copy numbers of STK11 in 3 of 18 individuals, significantly more often than in control subjects (51). Of interest, STK11, also known as liver kinase B1, triggers phosphorylation of tau (52), and amyloid precursor protein overexpression promotes tau phosphorylation in an liver kinase B1-dependent manner (53).…”
Section: Genetics Of Psychosis In Alzheimer’s Diseasementioning
confidence: 96%
“…Large CNVs containing CEBPB or CEBPD and hundreds of genes have been associated as pathogenic for developmental delay phenotypes, but smaller CNVs-containing regions with only the CEBPB or CEBPD genes and few adjacent genes are not suspected to be pathogenic (Kaminsky et al 2011). One study has reported frequent loss of one allele (hemizygosis) in the CEBPD locus in familiar schizophrenia patients (Lee et al 2010a). Gene copy amplification of CEBPD has been associated with glioblastoma ) and loss of heterozygosity in a region containing the CEBPD gene in one patient with atherosclerosis (Sleptsov et al 2014).…”
Section: Polymorphisms In the Human Cebpb And Cebpd Genesmentioning
confidence: 96%
“…Moreover, RNA sequencing can quantify the transcripts with an absolute number value, rather than yielding a relative value as in microarray. Other research has suggested, even though relatively uncommon, that copy number variation (CNV) deletions or replications can lead to variable gene expression and cause schizophrenia with symptoms of differing severity [77, 78]. Thus, one of the limitations of our study is that, by using a RNA microarray, these CNV could not be detected.…”
Section: Discussionmentioning
confidence: 84%